Telelactation Counseling Outcomes Among Midwifery Students: An International Collaborative Community Service Program to Improve Exclusive Breastfeeding Support - Kurniati Devi Purnamasari; Zahrah Saad; Siti Fatimah; Eet Sumiati; Nurul Hidayah; Luthfiyatun Thoyyibah; Lista Listiawati; Elia Nurkamelia; Adhelia Dwi Lestari (International Journal of Community Service (IJCS), 2026)
The Collaborative Community Service Excellence Program entitled “Telelactation Counseling Outcomes Among Midwifery Students: Collaborative Community Service with MAHSA University to Improve Exclusive Breastfeeding in Postpartum Mothers” was developed to address the increasing need for innovative breastfeeding support strategies and digital health integration in maternal healthcare services. This program aimed to enhance midwifery students’ competencies in telelactation counseling while strengthening international academic collaboration between Universitas Galuh, Indonesia, and MAHSA University, Malaysia. The program involved 40 participants consisting of 36 undergraduate midwifery students from Universitas Galuh and 4 students from the Advanced Diploma in Midwifery Program of MAHSA University. The implementation was conducted through three stages, namely the Pre-Counseling Phase, Synchronous Teleconference Counseling, and Post-Counseling Monitoring. Learning activities included academic sharing, mentoring, collaborative discussions, simulation-based practice, and evaluation sessions. The results demonstrated a significant improvement in participants’ knowledge regarding telelactation counseling, exclusive breastfeeding support, and digital health applications. The proportion of participants with good knowledge increased from 20.0% in the pre-test to 75.0% in the post-test, while the mean knowledge score improved from 65.40 ± 12.35 to 84.75 ± 8.21 (p < 0.001). In addition, the program enhanced intercultural communication, expanded institutional networking, and promoted sustainable international collaboration. In conclusion, the program effectively improved participants’ competencies in telelactation counseling and contributed to the dissemination of innovative telehealth approaches to support exclusive breastfeeding and maternal-child healthcare services.